EFEK PEMACUAN APOPTOSIS FRAKSI ETIL ASETAT EKSTRAK ETANOL AKAR PASAK BUMI (Eurycoma longifolia Jack) TERHADAP SEL HeLa - Isnaniati Romadhoni Indarwati Nurkhasan (Farmasains : Jurnal Farmasi dan Ilmu Kesehatan, 2012)
Pasak bumi is one of the Indonesian original plants having anticancer activity. Eurycomanone was isolated from Eurycoma longofolia, Jack root was proven to have cytotoxic effect and induce apoptosis on Hela cells. The objective this study was to know the cytotoxic activity of ethyl acetate fraction of ethanolic extract of the Eurycoma longifolia, Jack root on Hela cells and the mode of death. Ethyl acetate fraction was obtained from the ethyl acetate soluble fraction from residue of chloroform fraction of ethanolic extract of Eurycoma longifolia Jack roots. The cytotoxic assay was performed using MTT test method with concentration series used in this study were 1000; 750; 500; 400; 200; 100; 50; 12,5; 6,25; 3,125; and 1,5625 µg/ml. Absorbance was measured at wavelength of 550 nm using ELISA reader. Apoptosis assay were observed using Giemsa staining. MTT assay indicated that etil asetat fraction of ethanolic extract of the Eurycoma longofolia, Jack root showed cytotoxic activity againts Hela cells with IC50 value 3,70 µg/ml. The result of apoptosis assay indicated that the ethyl acetate fraction of ethanolic extract of the Eurycoma longofolia, Jack root induce apoptosis. The apoptotic cells was observed wrinkle, rounded and dark colors leading to chromatin condensation.